The road to capital account liberalization: How emerging markets defend their interests in the global financial order - Huang, Y (2021)
As free capital mobility is an essential characteristic of the global financial order, whether emerging markets liberalize their capital account is a topic that has aroused wide discussion. Even though many scholars propose the general trend to liberalization because the international system constrains state behavior, some emphasize that emerging markets would make resistance because of their discontent toward volatile capital mobility. However, neither could fully explain two interesting phenomena: first, when the financial order's coercion culminated, some countries could independently maintain restrained liberalization. Second, after the order has confronted a legitimacy crisis, China unexpectedly accelerated the liberalization even if it has long maintained the restriction.